ANALISIS VALUE FOR MONEY DENGAN PENDEKATAN EFEKTIVITAS PADA KINERJA KEUANGAN KOTA SEMARANG PADA TAHUN ANGGARAN 2017-2021 - Erlinda Nur Aulia; Agustina Prativi Nugraheni (Transpublika Publisher, 2022)
This research was conducted with the aim of knowing the level of effectiveness of the Semarang City Government's financial performance in the 2017-2021 fiscal year through Value for Money analysis. The research method used in this study is the Quantitative Descriptive Method. The data needed in this study was obtained through the PPID website of the Semarang City Government in the form of a Budget Realization Report and Notes to Financial Statements. Based on the measurements that have been carried out, it is stated that the average measurement results obtained within a period of 5 years from 2017 to 2021 reached the effective criteria with an average achievement of 97.82%, which means that during those 5 years the Semarang City Government has achieved success in carrying out tasks to achieve goals.